Financial Performance Analysis On PT. Asuransi Jiwa Syariah Bumiputera - Ahmad Riyadi Siregar; Sugianto Sugianto; Laylan Syafina (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2021)
The method used in writing this research uses a quantitative method. In analyzing and processing data using the financial ratio method, namely by calculating the profitability ratios (ROA, ROE, and NPM) and liquidity ratios (Current Ratio, Quick Ratio and Cash Ratio). The purpose of this study is to utilize insurance financial ratio analysis,  to access the financial condition of PT. AJS Bumiputra available at www.bumiputrasyariah.co.id during the 2016-2019 period, and to compare the financial statements of PT. AJS Bumiputra from 2016 so that it can be seen the change in value that occurs, whether it is an increase or a decrease. Based on the research results, it can be concluded that the financial condition of PT. AJS Bumiputra based on this research not from www.bumiputrasyariah.co.id. The profitability ratio is categorized as poor because the ROA, ROE and NPM values ??are still in a minus condition, and the company has not been able to generate profits from all company assets. However, the liquidity ratio is categorized as good, because the values ??of the CR, Quick Ratio and Cash Ratio are still in a safe condition, meaning that the company is still able to pay/cover all short-term debts/liabilities. The comparison of the value of the asset component during the 2016-2019 period tends to fluctuate. Compared to the average assets of the sharia insurance industry in Indonesia, the assets owned by PT. AJS Bumiputra still has to be improved again in order to continue to compete in the midst of the development of the sharia insurance industry in Indonesia.